BUILDING INDONESIA’S NATIONAL CYBER DEFENSE AND SECURITY TO FACE THE GLOBAL CYBER THREATS THROUGH INDONESIA SECURITY INCIDENT RESPONSE TEAM ON INTERNET INFRASTRUCTURE (ID-SIRTII) - Adi Rio Arianto; Gesti Anggraini (Jurnal Pertahanan & Bela Negara, 2019)
The establishment of the “Indonesia Security Incident Response Team on Internet Infrastructure (ID-SIRTII)” is a tactical step by the Indonesian Ministry of Information and Communication to ensure the stability of national information regarding cyber protection and all forms of threats. This study explores the urgency of ID-SIRTII to prevent global cyber threats. The study found that cyber threats in Indonesia are very complex, seeing the variations of actors, motives, and targets (civil or military purpose). This complexity can be explained through the following four aspects, namely : (1) by understanding of Geometripolitic studies in cyber, there are at least two domains that can be reached, namely “the using of cyber for high-politics purposes (military)”by formulating and activating of Cyberpower to face the Global Cyber War(PSG), Wold Geometri War (PGA), and the forming of “Siber State or Siber Government”; and “the use of cyber for low-politics purposes (civil)”by the protection of civil activities in cyberspace; (2) in order to prevent the spread of national cyber crime, the implementation of the ID-SIRTII policy is integrated with the national cyber institutions; (3) in order to prevent the Global Cyber Threat, the implementation of ID-SIRTII policies needs to be strengthened and well-integrated with the regional and global cyber institutions; and (4) considering of the two “functionalism of cyber” also to form a structuralism of Indonesian National Defense and Security system in the cyber sector, nowdays Indonesia needs to build a CyberForce as a complement to the Army, Navy, and Air Force.Keywords: defense, security,cyber, ID-SIRTII, cyber force